Alcohol and drugs consumption and associated psychosocial factors in Lima adolescents - SALAZAR, EDUARDO (2004)
Objective: To determine the prevalence of alcohol and drug use and psychosocial factors associated in adolescents in Lima. Design: Analytic transversal study. Material and Methods: A sample of 430 adolescents from one Lima high school was studied. The questionnaire used was the Personal Experience Screening Questionnaire (PESQ). Results: Three hundred and ninety-one valid questionnaires were received. The prevalence of either alcohol or drug use was 43%; the alcohol use 42,2%, marijuana 8,7%, and cocaine 3,1%. The problem of alcohol or drug use was 10,7%. The psychosocial factors associated were psychological distress (OR 4,58 CI 95% 1,60-13,05), severe thinking problem (OR 2,63 CI 95% 1,15-6,01), and physical abuse (OR 2,31 CI 95% 1,19-4,49). Conclusions: The psychosocial factor most associated with drug use was severe psychological distress. Furthermore, an association between both thinking problem and physical abuse with drug use was found. Sexual harassment was found to be associated only in second year high school adolescents.